Antibacterial activity of shrimp chitosan against some local food spoilage bacteria and food borne pathogens (Bangladesh Journal of Microbiology, 2012)
The objective of this study was to determine the more efficient antibacterial activity of chitosan among irradiated and nonirradiated form. Chitin was isolated from shrimp and then converted into chitosan. The initial molecular weight of chitosan was 1.6 X 106 Da and after step by step pretreatments using alkali, acid and H2O2, the final molecular weight was found to be reduced to 2.7 X 104 Da and the degree of deacetylation (DD) was 70%. Chemical treatments deproteinated and decalcified the chitin. Chitosan, the deacetylated form of chitin, was dissolved in lactic acid and then irradiated to perform antimicrobial activity. To conduct the experiment, seven different strains of bacteria were isolated from spoiled orange and it was found that chitosan was more effective to inhibit the growth of these bacteria. The more efficient result was found with irradiated chitosan than the non-irradiated one and the efficiency was consistently along with the increasing   of the radiation dose. The best antimicrobial activity was observed with 32 kGy. DOI: http://dx.doi.org/10.3329/bjm.v28i1.11809 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 45-47